A novel 1x2 multimode interference optical wavelength filter based on photodefinable benzocyclobutene (BCB 4024-40) polymer - Ibrahim, Mohd. Haniff (Wiley InterScience, 2007)
A novel 1 Ã— 2 multimode interference (MMI) optical wavelength filter for 1310 and 1550 nm operation based on photodefinable BenzoCyclobutene (BCB 4024-40) polymer is demonstrated. The device is fabricated on BK7 glass substrate with thin layer of SiO2 as cover. A cost effective chemical etching technique is used in the fabrication process to take advantage of the photosensitive nature of the polymer. The filter length is significantly reduced by adopting the restricted MMI scheme, lower beat length ratio, and cascaded MMI couplers. At 1550 nm filtering operation, the measured crosstalk is -20.6 dB and at 1310 nm filtering is -14.4 dB. The measured insertion loss is around 3.2-3.5 dB for both ports.